2010
DOI: 10.1016/j.jbiomech.2010.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Response of able-bodied persons to changes in shoe rocker radius during walking: Changes in ankle kinematics to maintain a consistent roll-over shape

Abstract: Recent studies have determined a seemingly consistent feature of able-bodied level ground walking termed the roll-over shape, which is the effective rocker (cam) shape that the lower limb system conforms to between heel contact and contralateral heel contact during walking (first half of the gait cycle). The roll-over shape has been found to be largely unaffected by changes in walking speed, load carriage, and shoe heel height. However, it is unclear from previous studies whether persons are controlling their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 11 publications
0
28
1
Order By: Relevance
“…For each subject and foot type, roll-over shapes were determined by transforming the COP data from a laboratory-based reference frame to the three-dimensional shank-based coordinate system [21]. Because the COP data progress forward from heel to toe during stance, while the shank is rotated over the foot, the roll-over shapes can be modeled as the lower half of a circle in the shank's plane of progression.…”
Section: Roll-over Characteristicsmentioning
confidence: 99%
“…For each subject and foot type, roll-over shapes were determined by transforming the COP data from a laboratory-based reference frame to the three-dimensional shank-based coordinate system [21]. Because the COP data progress forward from heel to toe during stance, while the shank is rotated over the foot, the roll-over shapes can be modeled as the lower half of a circle in the shank's plane of progression.…”
Section: Roll-over Characteristicsmentioning
confidence: 99%
“…Similarly, the present study found no significant differences between the male and female subjects. In a study that analyzed the gaits of persons who were wearing gait assisters with flat shoe soles and those who were wearing gait assisters with slightly bent shoe soles, signifi- cant differences were reported in the dorsal flexion of the ankle and gait velocity which were related to the degrees of flatness and bend of the shoe soles 25) . Gait velocity would increase if the shoe soles of crutch walkers had bent heels to facilitate heel strikes during four-point crutch gait, which is slow but the safest for persons using crutches.…”
Section: Discussionmentioning
confidence: 99%
“…Their experimental studies found that the AFROS remains the same irrespective of changes in walking speed , heel height and load carriage (Hansen and Childress, 2005). They also found that a person controls the ankle kinematics to maintain a consistent ROS (Wang and Hansen, 2010) and that in the case of a trans-tibial prosthesis user, an alignment for better walking performance for a given type of prosthetic foot can be determined using this ROS (Hansen et al, 2000). Srinivasan et al (2009) used Hansen's ROS in a forward dynamics model for the gait of trans-tibial prosthesis users.…”
Section: S Mohan Varma and S Sujatha: Segmental Contributions Tomentioning
confidence: 96%